Photocatalytic Oxidation of Aqueous Ammonia Using Atomic Single Layer Graphitic‑C3N4 - Wang, Hua; Su, Yan; Zhao, Huanxin; Yu, Hongtao; Chen, Shuo; Zhang, Yaobin; Quan, Xie (Environmental science & technology, 2014)
Direct utilization of solar energy for photocatalytic removal of ammonia from water is a topic of strong interest. However, most of the photocatalysts with effective performance are solely metal-based semiconductors. Here, we report for the first time that a new type of atomic single layer graphitic-C3N4 (SL g-C3N4), a metal-free photocatalyst, has an excellent photocatalytic activity for total ammonia nitrogen (TAN) removal from water. The results demonstrated that over 80% of TAN (initial concentration 1.50 mg·L–1) could be removed in 6 h under Xe lamp irradiation (195 mW·cm–2). Furthermore, the SL g-C3N4 exhibited a higher photocatalytic activity in alkaline solution than that in neutral or acidic solutions. The investigation suggested that both photogenerated holes and hydroxyl radicals were involved the TAN photocatalytic oxidation process and that the major oxidation product was NO3 –-N. In addition, SL g-C3N4 exhibited good photocatalytic stability in aqueous solution. This work highlights the appealing application of an inexpensive metal-free photocatalyst in aqueous ammonia treatment.